2017
DOI: 10.1016/j.jnoncrysol.2016.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric and mechanical behavior of NaNbO3/PEKK lead-free nanocomposites

Abstract: a b s t r a c tLead-free piezoelectric nanocomposites based on poly(ether ketone ketone) (PEKK) and sodium niobate (NaNbO 3 ) particles were elaborated. The presence of submicronic particles does not influence the thermal stability of the matrix so that no degradation phenomenon is observed before 500°C. The conservative mechanical modulus G′ increases linearly with the NaNbO 3 fraction; this variation is well fitted by the Kerner model until 20 vol%. Such nanocomposites remain ductile. The polarizing field re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…7 shows the PEKK thermogram over ail the temperature range. The study of the mechanical relaxations have been extensively detailed in a previous paper [ 48].…”
Section: Influence Of Graphene On the Mechanical Properties Below Thementioning
confidence: 99%
“…7 shows the PEKK thermogram over ail the temperature range. The study of the mechanical relaxations have been extensively detailed in a previous paper [ 48].…”
Section: Influence Of Graphene On the Mechanical Properties Below Thementioning
confidence: 99%
“…Second, as P(VDF‐TrFE) is on the rubbery plateau at room temperature, the Ag@Ni NWs’ presence induces additional topological nodes, which increase the rubbery mechanical modulus. It has been previously shown that such modulus increase leads to a transduction/dissipation phenomenon and d 33 coefficient [ 34 ] decrease. This phenomenon coupled with a lower effective field caused by dielectrical losses and a lower crystallinity ratio explains such a d 33 decrease.…”
Section: Resultsmentioning
confidence: 99%
“…We observe an increase of 27% for the unsized composite compared to the matrix. This energy loss mechanism involves a stick–slip effect . This effect which is present in a wide range of composites, indicates a specific dissipative energy due to the creation and disruption of physical bonds between the matrix and the fibrous reinforcement.…”
Section: Resultsmentioning
confidence: 99%
“…This energy loss mechanism involves a stick-slip effect. 21,[39][40][41] This effect which is present in a wide range of composites, indicates a specific dissipative energy due to the creation and disruption of physical bonds between the matrix and the fibrous reinforcement. Figure 6 represents tan δ as a function of temperature for the unsized composite ( ), and the PEKK matrix ( ).…”
Section: Dynamic Mechanical Relaxationmentioning
confidence: 99%